Comparison of salter osteotomy results in two different age groups in the treatment of developmental hip dislocation - Özkan, Sezai; Adanaş, Cihan (Journal of Surgery and Medicine, 2020)
Aim: Surgical treatment of developmental hip dislocation is highly challenging in children of walking age. The most common complications following surgery include avascular necrosis and redislocation. In this study, we aimed to compare the preoperative and postoperative acetabular index, avascular necrosis (AVN) and redislocation rates between two age groups of open reduction and Salter osteotomy in DDH (Developmental Dysplasia of the Hip). Methods: This prospective cohort study included patients who underwent open reduction and salter osteotomy for DDH between 2014 and 2017. Patients were grouped based on age as follows: Group 1: 18 -30 months old (n=44), Group 2: 31-48 months old (n=41). Preoperative, postoperative, and final acetabular indexes, AVN and redislocation rates were compared. Results: Among 85 patients included in the study, 20 were male and 65 were female. The mean ages of Groups 1 and 2 were 21.6 months and 38.5 months, respectively. Following surgery, Group 1 mean acetabular index reduced to 25.9 degrees from 35.1 degrees, while that of Group 2 decreased to 22.1 degrees from 33 degrees. AVN was present in 10 patients (22.72%) in Group 1 and 4 patients (9.75%) in Group 2. Conclusion: The acetabular index was adequately corrected in both groups. AVN was more frequent in children who had early interventions. We believe that the higher rate of avascular necrosis in children who underwent early intervention is due to surgical technique and using tighter sutures in the hip joint capsule.